One-Year Results for the ROBUST III Randomized Controlled Trial Evaluating the Optilume® Drug-Coated Balloon for Anterior Urethral Strictures. Issue 4 (2nd April 2022) - Elliott, Sean P.; Coutinho, Karl; Robertson, Kaiser J.; D'Anna, Richard; Chevli, Kent; Carrier, Serge; Aube-Peterkin, Melanie; Cantrill, Christopher H.; Ehlert, Michael J.; Te, Alexis E.; Dann, Jeffrey; DeLong, Jessica M.; et al.
Abstract : Purpose: The Optilume® drug-coated balloon (DCB) is a urethral dilation balloon with a paclitaxel coating that combines mechanical dilation for immediate symptomatic relief with local drug delivery to maintain urethral patency. The ROBUST III study is a randomized, single-blind trial evaluating the safety and efficacy of the Optilume DCB against endoscopic management of recurrent anterior urethral strictures. Materials and Methods: Eligible patients were adult males with anterior strictures ≤12Fr in diameter and ≤3 cm in length, at least 2 prior endoscopic treatments, International Prostate Symptom Score ≥11 and maximum flow rate <15 ml per second. A total of 127 subjects were enrolled at 22 sites. The primary study end point was anatomical success (≥14Fr by cystoscopy or calibration) at 6 months. Key secondary end points included freedom from repeat treatment, International Prostatic Symptom Score and peak flow rate. The primary safety end point included freedom from serious device- or procedure-related complications. Results: Baseline characteristics were similar between groups, with subjects having an average of 3.6 prior treatments and average length of 1.7 cm. Anatomical success for Optilume DCB was significantly higher than control at 6 months (75% vs 27%, p <0.001). Freedom from repeat intervention was significantly higher in the Optilume DCB arm. Immediate symptom and urinary flow rate improvement was significant in both groups, with the benefit being more durable in the Optilume DCB group. The most frequent adverse events included urinary tract infection, post-procedural hematuria and dysuria. Conclusions: The results of this randomized controlled trial support that Optilume is safe and superior to standard direct vision internal urethrotomy/dilation for the treatment of recurrent anterior urethral strictures <3 cm in length. The Optilume DCB may serve as an important alternative for men who have had an unsuccessful direct vision internal urethrotomy/dilation but want to avoid or delay urethroplasty.